2010
DOI: 10.1080/00103620903494343
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid–Induced Growth and Biochemical Changes in Salt‐Stressed Wheat

Abstract: The interactive effect of salicylic acid and sodium chloride (NaCl) salinity on wheat (Triticum aestivum L.) cv. 'Inqlab' (salt-sensitive) and cv. 'S-24' (salt-tolerant) was studied in a sand-culture pot experiment in a net house. Wheat seeds soaked in water and 100 ppm salicylic acid solution for 6 h were sown in sand salinized with 0, 50, and 100 mM NaCl. Pots were irrigated with quarter-strength Hoagland's nutrient solution. Fourteen-day-old seedlings were harvested, and growth parameters (leaf and root l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Entesari et al (2012) reported the same effect on the mung bean grown under salinity stress and primed with SA. Hamid et al (2010) reported that SA priming of wheat seeds under salinity stress resulted in the production of more vigorous and larger seedlings and enhanced chlorophyll, dissolved sugars and proteins content of the plant. The positive effect of SA treatment on seedling growth under salinity stress could probably be caused by the involvement of this growth regulator in cell division (Shakirova et al, 2003;Dolatabadian et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Entesari et al (2012) reported the same effect on the mung bean grown under salinity stress and primed with SA. Hamid et al (2010) reported that SA priming of wheat seeds under salinity stress resulted in the production of more vigorous and larger seedlings and enhanced chlorophyll, dissolved sugars and proteins content of the plant. The positive effect of SA treatment on seedling growth under salinity stress could probably be caused by the involvement of this growth regulator in cell division (Shakirova et al, 2003;Dolatabadian et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in accordance with previous studies. Many researchers have reported that accumulation of sugar and proline was enhanced in response to environmental stresses 22, 33, 34. It is possible to say that enhanced proline and sugar content might be contributing mitigating effects of MSH under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in growth in salt‐stressed plants are well documented and are mainly attributed to water deficit, nutritional imbalance and specific ion toxicity 1, 2. Besides, it is possible that salt‐stressed plants utilize energy for osmotic adjustment processes at the cost of growth 2, 22. Improvement of seedling growth in salt‐stressed seeds in response to MSH may be related to the induction of metabolic activity containing synthesis reactions and enzyme activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas application of SA enhanced germination percentage by 13.05%, vigor index by 68.60%, mean germination time by 39.74% compared to respective NaCl treatments (Alamri et al, 2018). Hamid et al (2010) reported that SA priming of wheat seeds under salinity stress resulted in the production of more vigorous and larger seedlings and enhanced chlorophyll, dissolved sugars and proteins content of the plant.…”
Section: Introductionmentioning
confidence: 99%